MUSLIMS' THOUGHTS OF NON-MUSLIMS' POLITICAL RIGHTS IN MAJORITY MUSLIM AREAS IN MAKASSAR - Usman Jafar (Jurnal Adabiyah, 2019)
This research endeavors to build an egalitarian social order that emphasizes human equality and eradicates all forms of discrimination based on identities created by the current social system, including race, religion, ethnicity, skin color, nationality, etc. This is done because research into issues of citizen equality within Muslim political systems is an interesting part of discourse regarding national diversity and ideological issues in governance. Using an empirical approach, this study analyzes the involvement of non-Muslims in practical politics and government in Muslim-majority areas such as Makassar. The involvement of non-Muslims in practical politics is key to the creation of a democratic system of governance. This study contributes an explanation as to why the recognition of non-Muslims' political rights must not solely be viewed in terms of theory, but also in terms of normative and practical structures, as Islam promotes democratic governance in which equality, justice, and tolerance are realized well and no political discrimination is committed against citizens. Through this, the purity of Islam can remain undistorted and the gap between the practiced reality among this Muslim-majority population and fundamental Islamic teachings can be bridged.